Determination of Dimensions of Glenoid Cavity from other Scapular Parameters - Khurram Shabeer, Motasim Billah, Abdul Hafeez Baloch, Mudassir Shahbaz, Nadia Majeed, Kanwal Sharif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Different pathological conditions are associated with the anatomical variations in glenoid cavity. For getting insights into these variations the anthropometric parameters knowledge is highly required. Objective: The purpose of the study was the determination of the anthropometric relationship present between the left and right side of the glenoid cavity of the scapula and the application of the obtained knowledge in the forensic medicine. Place and Duration: In the department of anatomy, Multan Medical and Dental College and Bacha Khan Medical Complex Swabi for six months duration, from January 2021 to June 2021. Material and Methods: The data of 190 patients included in the study, was collected from the anatomy department of our institute. The sample was withdrawn from the non-deformed and well macerated scapulae bone of the 190 patients. The calibrated sliding digital caliper was used to measure the anthropometric parameters of glenoid cavity. The glenoid height, width and index were calculated by SPSS software. Results: The 34.8±4.0 (R=38 ± 4.98 and L=27.9-46.78) and 24.9 ±3.90 (R=27.2 ± 3.43 and L=20.1- 36) was the calculated mean standard deviation of Maximum glenoid height (MGH) and Maximum glenoid width (MGW) respectively. The statistically significant and greater values of MGH and MGW on the right side were obtained by using ANOVA and t-test. While calculated values of glenoid Index (GI) was smaller on the right side as compared to the left. Conclusion: The kinanthropological applications of the scapula are indicated by the study that which side can be more commonly used. This study provides with in-depth knowledge of biological profiling and develops better understanding required during reconstruction of the damaged skeleton. Keywords: Glenoid cavity, Maximum glenoid height (MGH), Maximum glenoid width (MGW).